2015
DOI: 10.1039/c4cc08231a
|View full text |Cite
|
Sign up to set email alerts
|

Water-soluble nickel-bis(dithiolene) complexes as photothermal agents

Abstract: The remarkable photothermal properties of pegylated nickel-bis(dithiolene) complexes in water can induce cell death under laser irradiation in the near infrared (NIR) region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 13 publications
2
39
0
Order By: Relevance
“…Release of CF from photothermosensitive EggPC/DSPE-PEG 2000 liposomes containing5wt %o fNi8C 12 complex in wateri nt he dark. [19] TheI C 50 of Ni8C 12 could not be determinedd ue to its strongh ydrophobicity.I n the case of Lp-Ni8C 12 ,c ytotoxicity is due only to the liposome and not to the encapsulatedc omplex, as the cytotoxicity is the same whether the complex is present or not (Figure 3). ChemMedChem 2017ChemMedChem , 12,1753ChemMedChem -1758 www.chemmedchem.org two cell lines (HeLa andM DA-MB-231)a fter 24 hi ncubation (see SI for details).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Release of CF from photothermosensitive EggPC/DSPE-PEG 2000 liposomes containing5wt %o fNi8C 12 complex in wateri nt he dark. [19] TheI C 50 of Ni8C 12 could not be determinedd ue to its strongh ydrophobicity.I n the case of Lp-Ni8C 12 ,c ytotoxicity is due only to the liposome and not to the encapsulatedc omplex, as the cytotoxicity is the same whether the complex is present or not (Figure 3). ChemMedChem 2017ChemMedChem , 12,1753ChemMedChem -1758 www.chemmedchem.org two cell lines (HeLa andM DA-MB-231)a fter 24 hi ncubation (see SI for details).…”
Section: Introductionmentioning
confidence: 98%
“…Mebrouk more, metal-bis(dithiolene) complexes are non-luminescent. [19] These complexes are also highly stable under NIR laser irradiation, andn op hotobleaching has been observed. [17,18] In addition, properf unctionalization of the complexes has allowed for very good aqueous solubility.M ore importantly,c ell-based experiments have demonstrated that NIR laser irradiation of cell culturesi ncubated with metal-bis(dithiolene) complexes can induce cell death.…”
Section: Introductionmentioning
confidence: 98%
“…6 The photothermal properties of water-soluble nickelbis(dithiolene) were also efficiently used in cellulo experiments to induce cell death under laser irradiation. 7 Several liquid crystalline systems build around metal-bis(dithiolene) core have been described in the literature. 8 But, the photothermal properties of this class of metal complexes have never been used to induce thermal transitions.…”
mentioning
confidence: 99%
“…For this purpose, a first series of metal‐bis(dithiolene) complexes functionalized with polyethylene glycol chains was synthesized (Figure ) . Polyethylene glycol chains have been selected for their good water solubility and their biocompatibility.…”
Section: Nanoparticlesmentioning
confidence: 99%
“…Toxicological data on metal‐bis(dithiolene) complexes are very limited and the pharmacokinetic of these complexes still have to be evaluated. The only information available is that the IC50 of a nickel‐bis(dithiolene) complex carrying eight triethylene glycol chains is around 500 µg/mL . The IC50 of nickel‐bis(dithiolene) complex carrying long carbon chains could not have been determined due to their strong hydrophobicity.…”
Section: Nanoparticlesmentioning
confidence: 99%